Karakterisasi Bioplastik dari Pektin Kulit Labu Kuning (Cucurbita moschata Durch) - Listyarini, Risnita Vicky; Susilawati, Puspita Ratna; Cahyaningrum, Rosalia; Tonapa, Nely (Hydrogen: Jurnal Kependidikan Kimia, 2020)
Pumpkin (Cucurbita moschata Durch) is one of the vegetable plants that are generally consumed as food. Pumpkin skin is a waste that has potential as a raw material for making bioplastics because it has pectin content. The characteristics of pectin that are gel become a reference in making bioplastics. Bioplastic synthesis consists of four steps, namely the making of pumpkin peel flour, pectin extraction, bioplastic synthesis, and bioplastic characterization. The experimental results show that pumpkin skin waste can be extracted with HCl solution and produce pectin in a ratio of0.1:10 grams (w/w). The results of FTIR spectra characterization showed that bioplastics included pectin which produced absorption of C = O carbonyl groups in 1645 - 1625 cm-1 and C-O stretch groups at 1101 - 1104 cm-1. Bioplastics produced have yellow characteristic. Pumpkin skin waste bioplastics are expected to be an alternative solution to the utilization of waste into products.